Experiences of people living with disorders of sex development and sex reassignment: Meta‐ethnography of qualitative studies - Muhammad Sani, Abdurrahman; Soh, Kim Lam; Ismail, Ismi Arif; Arshad, Mohd Mursyid; Mungadi, Ismaila Arzika; Yau, Samira Labaran; Soh, Kim Geok (Wiley, 2019)
Aim The aim of this study was to synthesize the experiences of people with disorders of sex development.